Pendidikan Kristen & Pembaratan: Kajian Terhadap Pendidikan Misi Protestan di Minahasa, 1830 - 1916. - Amos Amos (Historiography: Journal of Indonesian History and Education, 2021)
The history of Christianity in Minahasa is closely related to colonialism. But colonialism not only affects the socio-political side of Minahasa society, but also the education system and schools. The history of Minahasa education is closely related to the activities of the Dutch Missionary Union or Nederlandsch Zendeling Genootschap (NZG). The implementation of educational programs, systems, and practices in Minahasa were carried out and pioneered by NZG, especially in the era of 1830 - 1918. Furthermore, we can see how Western-style education and NZG support intersect with various political dynamics in Dutch East Indies. Through historical research, this article examines the relationship between Western-style education and political dynamics of the Dutch East Indies in Minahasa society. This article offers an explanation and reflection in particular on mission education in Minahasa in relation to colonialism, the Western-style education system, the contribution of education, to the impact of education on the Minahasa community.Sejarah kekristenan di Minahasa berkelindan dengan kolonialisme. Tetapi kolonialisme bukan hanya mempengaruhi perkara sosial politik dalam masyarakat Minahasa, tetapi juga sistem pendidikan dan sekolah-sekolah yang terdapat di Minahasa. Sejarah pendidikan Minahasa begitu lekat kaitannya dengan kegiatan Serikat Misionaris Belanda atau Nederlandsch Zendeling Genootschap (NZG). Pelaksanaan program, sistem, dan praktik pendidikan yang di Minahasa banyak dilakukan dan dirintis oleh NZG, terutama dalam era 1830 - 1918. Lebih jauh lagi, NZG juga menjadi penyokong pendidikan ala Barat di Minahasa dengan menyediakan berbagai sarana hingga sumbangan pendidikan. Sehingga kita bisa melihat bagaimana pendidikan ala Barat dan dukungan NZG beririsan dengan berbagai dinamika politik Hindia Belanda. Melalui penelitian sejarah, artikel ini mengkaji relasi pendidikan ala Barat dengan dinamika politik Hindia Belanda dalam masyarakat Minahasa. Artikel ini menawarkan eksplanasi dan refleksi khususnya mengenai pendidikan misi di Minahasa dalam relasinya dengan kolonialisme, sistem pendidikan ala Barat, sumbangan pendidikan, hingga pengaruh pendidikan tersebut bagi masyarakat Minahasa.